Dual-Class Share Structure in the Indonesian Equity Market - Seroja, Triana Dewi; Tan, David; Fitri, Winda; Rusdiana, Shelvi (Lentera Hukum, 2023)
A lot of major equity markets abroad have allowed the listing of the Dual-Class Share Structure (DCSS) corporations. DCSS is an agreement in which two types of shares are issued by the very same firm, with one type of share conferring greater power compared to the other. The Indonesian Stock Exchange only allows for limited access for DCSS technology-related corporations to list on its Mainboard. To remain attractive as Southeast Asia's top financial centre, Indonesia needs to alter its securities regulations while making its listing market adaptable to meet the needs of various enterprises. This research aims to analyse and elaborate on permitting DCSS corporations to go public and devise suitable governance safeguards to guarantee the highest possible standards of corporate governance are upheld. This research explores the legal certainty and applicability of DCSS in the Indonesian equity market and abroad, using a qualitative approach and thematic analysis of secondary data. The major finding of this research is the acceptance of DCSS adds to issues with abuse of power by the controlling shareholders, which was outweighed by their cash flow rights. While those in favour of DCSS argue that the existing shareholders' main reason for choosing a DCSS arrangement is to preserve company control. Most major exchanges in the world have taken action to accommodate DCSS going public, like those in the USA, Hong Kong, Singapore, and China. Considering the magnitude of the Asian market, Indonesia can emulate the accomplishments of other exchanges too. A series of recommendations are provided to guarantee the highest standards of corporate governance can be upheld, such as: permitting DCSS for new entrants and innovative businesses, regulating the ownership of enhanced voting shares, and setting out sunset provisions for DCSS arrangement.Keywords: Company Law, DCSS, Dual-Class Shares, Equity Market.